Changes in Ovarian Function after Intrauterine Infusion of the Filtrate of Bacteria-Culturing Media in Cows with Undergrown Follicles - OHCHI, Takaharu; KAWAKAMI, Shizuo; SHINO, Masao (The Japanese journal of animal reproduction, 1991)
The filtrate of bacteria-culturing medium was infused into the uterus of cows having subfunctional ovaries. The bacteria were isolated from the uterine cervix of a cow. As a result, follicular development, estrus-like behavior and cervical mucus secretion were induced, suggesting the elevation of estrogen levels. Though the ovarian volume increased, the follicles did not fully develop as ones during an estrus stage and were soft and irregularly shaped. Ovulation and corpus luteum formation were not observed. The ovary may have capacity to respond to bacterial infection in the uterus with an increase in estrogen secretion.